Manajemen Strategik Kepemimpinan Dalam Meningkatkan Kualitas Guru SMP di Kabupaten Karawang - Abduloh Abduloh; Bambang Ismaya (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
LEADERSHIP STRATEGIC MANAGEMENT IN IMPROVING THE QUALITY OF JUNIOR HIGH SCHOOL (SMP) TEACHERS IN KARAWANG. Education at the secondary level is a first step in a journey of a protege life where this is a serious thing in a management of an educational institution at the junior level (SMP). Therefore an education at junior level requires a competitive leadership quality in being able to build a new strategy in improving teacher quality. If observed the quality of junior high school teachers in Karawang regency in particular requires a freshness in an education management process, where every educational institution requires a leader figure who can improve the teachers quality. Thus, a school leader must have a strategic in managing teachers and staff. So this study aims to determine the extent to which strategic management has been done in improving the quality of junior high school teachers in Karawang. Research method used is descriptive qualitative. The research was conducted on the leader in junior high school in Karawang regency, with research time from March to December 2015. While in the preparation of this study, the authors take field research where to obtain accurate and objective data, the researchers come directly to the location of research that is in Karawang regency.